Financial planning required to keep elephants in zoos in the United Kingdom in accordance with the Secretary of State's Standards of Modern Zoo Practice for the next 30 years. Issue 1 (25th March 2019) - Sach, F.; Fitzpatrick, M.; Masters, N.; Field, D.
Abstract : In June 2017, the Secretary of State's Standards of Modern Zoo Practice (SSSMZP) were updated with an appendix relating specifically to elephants (Appendix 8.8: Elephants). This update was published to bring elephant management standards in line with recognized advancing best practice. All zoos in the UK holding elephants are inspected against the new appendix, in accordance with the Zoo Licensing Act 1981, by dedicated Department for Environment, Food and Rural Affairs (Defra)‐appointed inspectors. Achieving the standards set out within the new appendix will require financial investment and careful planning from all the zoos holding elephants within the UK. At the time of writing, the annual cost of keeping a breeding group of elephants at ZSL Whipsnade Zoo, UK, was calculated from data collected over the last 10 years and the financial investment required to achieve SSSMZP compliance was estimated. The commercial benefit that elephants bring to ZSL Whipsnade Zoo was also quantified using feedback from visitor surveys. The cost of keeping a breeding herd of elephants at ZSL Whipsnade Zoo was estimated at £593 021–£641 863 per year, excluding indirect staffing costs, ground rent and contributions made by the Zoological Society of London (ZSL) to field‐conservation projects. Costs for achieving SSSMZP compliance will be considerably greater with substantial capital investment required. The commercial benefit was found to be extensive; with predicted significant increased visitor dwell time and secondary spend in the presence of elephants. Using ZSL Whipsnade Zoo as an example, this paper aims to consider holistically the financial costs when planning and implementing an optimum, welfare‐centred, sustainable future for elephants in zoos. Abstract : Using ZSL Whipsnade Zoo, UK, as an example, the financial costs when planning and implementing an optimum, welfare‐centred, sustainable future for elephants in zoos are considered. The annual cost of keeping a breeding group of elephants at ZSL Whipsnade Zoo was calculated at £593 021–£641 863 per year, excluding indirect staffing costs, ground rent and contributions made by the Zoological Society of London (ZSL) to field‐conservation projects. Additionally, the financial investment required to achieve Secretary of State's Standards of Modern Zoo Practice compliance was estimated. At ZSL Whipsnade Zoo, not only is there a clear commercial argument for continuing to have elephants but also there is certainty that these animals provide substantial opportunities for education, conservation research and fundraising. As the welfare standards required for elephants continue to increase in line with modern best practice, zoos must consider the full implications before deciding whether to continue to have elephants. (Photo: ZSL Whipsnade Zoo)